Gender role congruity and crowdfunding success. (31st August 2021) - Cowden, Birton J.; Creek, Steven A.; Maurer, Joshua D.
ABSTRACT: Research on financial resource acquisition has indicated negative consequences for entrepreneurs that act feminine when trying to attract investors. Yet, does this remain true in crowdfunding, where there is a more diverse population of backers? To explore this, we take a gender role congruity perspective to see if gender roles align with crowdfunding success. More specifically, 2, 071 entrepreneurs from Kickstarter were rated based on feminine (agreeableness and humility) and masculine (assertiveness and emotional stability) characteristics, and these characteristics were compared to whether or not the entrepreneur met the campaign goal. The results suggest that gender role congruity is a factor for successful crowdfunding, in that, for the most part, female entrepreneurs are rewarded for being more feminine and male entrepreneurs are rewarded for being more masculine. Only assertiveness was expected for both male and female entrepreneurs. Theoretical and practical implications are discussed from these findings.